Effect of piperine and its analogs on pharmacokinetic properties of sorafenib tosylate: Bioanalytical method development and validation - Anshuly Tiwari, Kakasaheb R. Mahadik, Satish Y. Gabhe (Journal of Applied Pharmaceutical Science, 2020)
Sorafenib tosylate (ST) is a drug of choice for the treatment of advanced hepatocellular carcinoma. The bioavailability of ST varies from 29% to 38% due to the presence of food, medication, and other factors. Moreover, the dose of ST (400 mg twice a day) is also higher due to its poor bioavailability. Piperine is known as a natural bioenhancer, and the use of a bioenhancer ultimately leads to a synergistic effect. In this study, the development and validation of a precise, accurate, and reproducible bioanalytical method was carried out using reversed-phase high-performance liquid chromatography (RP-HPLC). The objective of the study is to determine the effect of piperine and its analogs on the pharmacokinetics of ST using rats. The dose of ST alone and in combination with piperine and its analogs, given orally to male Wistar rats in suspension form, and the drug plasma concentration was examined using a validated RP-HPLC bioanalytical method. The separation of piperine and ST was achieved on the Chromatopak basic C18 HPLC column with the dimension of 250 mm × 4.6 mm × 5 μm, guarded along with the phenomenex guard column using ACN:Water:Formic Acid (70:29.5:0.5 v/v) as the mobile phase at 280 nm (isosbestic point of piperine and ST). The pharmacokinetic data of ST, along with piperine, exhibit a significant increase in area under the curve (AUC) of ST (1.66-fold), while the two derivatives of piperine (5a and 5d) exhibited almost double the increase in AUC compared to piperine (2.58 and 2.42-fold, respectively).
Keywords: Sorafenib tosylate (ST), piperine, bioenhancer, cancer, hepatocellular carcinoma, pharmacokinetics, bioavailability.